Perspektiver på hva en førskolelærer trenger å kunne om religion: Rammeplananalyse og preskriptive innspill - Bengt Ove Andreassen (Nordisk Barnehageforskning, 2011)
Title: Perspectives on what a preschool teacher need to know about religion: Curriculum analysis and prescriptive suggestions. Abstract: What does a pre-school teacher need to know about religion? This question is discussed in two separate parts of the article. The first part is a curriculum analysis of the framework surrounding Early Childhood Education and the three year undergraduate program for pre-school teachers in Norway. The analysis leads to a critical discussion on the bias towards Christian values in this framework. The second part of the article is prescriptive, answering the article’s research question. The outline of what a pre-school teacher’s competence on religion should consist of draws on the analysis and critical discussion in the first part. Here, arguments for including perspectives drawn from secular academic Religious studies in the three-year undergraduate program for pre-school teachers are presented. The main argument is that perspectives from Religious studies will ensure equal treatment of all religions and life views, and thus ensure the teaching to be in accordance with international conventions regarding human rights, which Norway are committed to.